Multi-Omics Exploration of the Role of PTGS2 as a Hub Gene in Ferroptosis Within the Artery of Takayasu Arteritis - Gao Q; Gao S; Li H; Chen Z; Zhang R; Li Y; Zhang H (Dove Medical Press, 2024)
Qing Gao,1,* Shang Gao,2,3,* Haiyang Li,1,* Zuoguan Chen,2 Ran Zhang,2 Yongjun Li,2 Hongjia Zhang1 1Department of Cardiovascular Surgery, Beijing Anzhen Hospital, Capital Medical University, Beijing, People's Republic of China; 2Department of Vascular Surgery, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 3Graduate School of Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Yongjun Li; Hongjia Zhang, Email liyongjun4679@bjhmoh.cn; zhanghongjia722@ccmu.edu.cnIntroduction: Takayasu arteritis (TAK) is an autoimmune disease affecting the aorta and its branches. Despite anti-inflammatory treatments, some patients require surgical vascular reconstruction due to rapid disease progression. The mechanisms behind persistent inflammation are unclear due to a lack of arterial samples. This study explores ferroptosis in TAK using high-throughput and single-cell transcriptomics.Methods: Transcriptomic data were collected from 8 TAK patients (2 for single cell RNA-seq and 6 for bulk RNA-seq) and 8 renal transplant donors, with single-cell data from 3 public carotid artery samples for control. Bioinformatic analysis was performed to identify ferroptosis-related genes in inflamed arteries.Results: We identified 1526 differentially expressed genes and 46 ferroptosis-related genes, with 6 genes including PTGS2 and HIF1A as hub genes. Single-cell analysis of 27,828 cells revealed increased M1-like macrophages, with PTGS2 highly expressed in these cells. Enrichment analysis indicated NF-κB signal pathway involvement.Conclusion: PTGS2 is a core ferroptosis-related gene in TAK vascular inflammation, highly expressed in M1-like macrophages, potentially upregulated via the IL1B-NF-κB pathway.Keywords: Takayasu arteritis, single-cell RNA sequencing, bulk RNA sequencing, ferroptosis, PTGS2